Palladium-catalyzed propargylative and allenylative dearomatization of 2-(chloromethyl)thiophenes: remarkable effect of solvents. Issue 1 (7th January 2016) - Ullah, Aziz; Zhang, Sheng; Bao, Ming; Yamamoto, Yoshinori; Almansour, Abdulrahman I.; Arumugam, Natarajan; Kumar, Raju Suresh
Abstract: Palladium-catalyzed a solvent-dependent product distribution in the propargylative and allenylative dearomatization reaction of 2-(chloromethyl)thiophenes with allenyltributylstannane under mild conditions is reported in this study. In the coordinating solvent acetonitrile, the propargylative dearomatization reaction selectively occurred to produce only the propargylic compounds with satisfactory to good yield. In the uncoordinating solvent dichloromethane, allenic compounds were obtained as major products with a small amount of propargylic compounds. Graphical abstract: The reaction selectivity could be easily controlled by the use of different solvents. The use of a coordinating solvent led to the formation of a propargylic compound as the sole product, whereas the use of an uncoordinating solvent led to the generation of an allenic compound as the major product.